Cyprus and the politics of property - Gürel, Ayla; Özersay, Kudret (My University, 2006)
The 'property issue' in the Cyprus problem has manifold implications. It concerns the individual rights and interests of around a third of the island's population, and will be central to economic and social considerations in the event of reunification. However, there are additional important political factors that have made the property issue into a key aspect of the Cyprus problem. Here we attempt to elucidate these factors by analysing the two Cypriot sides' official positions in relation to the property issue. We try to show how the two sides have managed to formulate their apparently irreconcilable positions in this area on the basis of the two ostensibly agreed principles of any prospective settlement, namely, the achievement of 'bizonality' in the Turkish Cypriot case, and the restoration of 'human rights' in the Greek Cypriot case. We also examine the way the two sides' leaderships and administrations have in effect guided and shaped the perceptions and expectations of the public along the lines of these positions by, among other things, presenting them as 'non-negotiable' or 'sacrosanct'.
Keywords: human rights; perception; political integration; social problem; Asia; Cyprus; Eurasia; Middle East